Investigation of Microvascular Complications of Type-2 Diabetes Mellitus Patients and its Clinical Outcome - Shahid Shehzad, Muhammad Zubair Khan, MS. Khushboo Chandio, Hamid Zafar, Rana Zohaib Munawar, Asif (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Diabetes mellitus type 2 is recognized as a global pandemic due to its substantially increasing prevalence. This metabolic disorder bears a significant potential incidence of microvascular complications (MVC) in chronic patients including neuropathy, retinopathy, and nephropathy which may prove fatal. Objectives: The study aimed to investigate the incidence of microvascular complications, its associated risk factors and comorbidities in the chronic diabetic population. Methods: This cohort was executed to assess the clinical records of visiting diabetic patients presented at PIMS hospital, Islamabad from July 2020 to June 2022. A total of 630 patients with T2DM of different age and sex groups, were included in the study and their clinical outcomes of MVCs were analyzed. Results: The overall incidence of MVCs was found 43.49% significantly (p<0.05) affecting the aged population with prolonged ailment, raised HbA1C of more than 8.5, raised BMI, hypertensive and genetically predisposed patients. The incidence was found high in females, aged population (more than 60 years), married, unemployed, urban population and the prolonged illness, overweight, hypertensive and genetically predisposed people with a family history had the highest incidence of MVC (p<0.05). Among the MVCs, the patients highly suffered (p<0.05) from neuropathy, followed by retinopathy and nephropathy due to persistent ailment of T2DM, hauled glycated hemoglobin, overweight and hypertensive population. Practical implication: This study paved the way for clinicians to instigate diabetic patients MVCs of neuropathy, retinopathy and nephropathy for the sake of health of patients and avoid such complications by screening out the associated risk factors and comorbidities Conclusion: Hence, it was concluded that microvascular complications were the major clinical outcome in T2DM patients. Therefore, managemental and preventive therapies at the earliest stage may delay the progression of MVCs in them and will revive their quality of life. Keywords: Glycated hemoglobin; Hypertension; Nephropathy; Neuropathy; Obesity; Retinopathy.